Analisis Kritis Teori Penetapan Harga Adam Smith - Rochma Aulia Supandi; Khoirul Umam (Jurnal Ekonomika dan Bisnis Islam, 2025)
This study aims to provide a critical analysis of Adam Smith's pricing concept from an Islamic economic perspective and offer a new framework for its Islamization. Although previous studies have discussed Islamic critiques of Smith's theory, most have been limited to descriptive comparisons without offering an integrated model for its application. This study differs by systematically mapping the components of Smith's pricing theory the role of the market, the role of government, business ethics, objectives, and pricing mechanisms and then reconstructing them into a practical Islamic pricing framework grounded in the principles of the Qur'an, hadith, and classical fiqh thought. This study employs a qualitative literature review method by synthesizing primary and secondary literature, categorizing concepts, and reinterpreting them through Islamic jurisprudence. The resulting framework not only highlights the theoretical gap between Smith's perspective and Islamic economics but also provides a structured reinterpretation that can be directly applied by policymakers and economic actors to ensure pricing practices align with Islamic ethical and legal standards.